2021
DOI: 10.3892/ol.2021.12583
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology‑based study to explore the mechanism of the Yiqi Gubiao pill in lung cancer treatment

Abstract: Lung cancer (LC) has been one of the most prevalent and fatal malignancies in the past 5 years. Yiqi Gubiao pills have a good clinical effect against LC. However, their complex composition limits proper understanding of their pharmacological mechanism. Therefore, the present study aimed to systemically explore the underlying mechanisms of Yiqi Gubiao pills in treatment of LC. The network pharmacology approach was employed to identify the active ingredients and LC targets associated with Yiqi Gubiao pills. Pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Asthma or airway inflammation‐related targets were identified by searching the Pubmed‐Gene (https://www.ncbi.nlm.nih.gov/pubmed/gene) 56 and GeneCards (http://www.genecards.org) 62 databases. Then, all information was consolidated and duplicate targets were removed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma or airway inflammation‐related targets were identified by searching the Pubmed‐Gene (https://www.ncbi.nlm.nih.gov/pubmed/gene) 56 and GeneCards (http://www.genecards.org) 62 databases. Then, all information was consolidated and duplicate targets were removed.…”
Section: Methodsmentioning
confidence: 99%
“…The Chemical Structure Depiction and SMILES string of ICA were found in the PubChem compound database (https://pubchem.ncbi.nlm.nih.gov/). The potential targets were screened from SEA (http://sea.bkslab.org), 56 CTD (http://ctd.mdibl.org), 57 HERB (https://herb.ac.cn), 58 PharmMapper (http://www.lilab-ecust.cn/pharmmapper/submitfile.html), 59 Symmap (http://www.symmap.org) 60 databases and the literature. Then, all targets were calibrated using the Uniprot (https://www.uniprot.org/) database 61…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, network pharmacology has become a powerful tool that can be combined with pharmacology [ 12 ]. This method has been shown to be an efficient way to explore the multiple components, targets, and pathways of TCM formulas [ 13 ]. For example, Cao et al [ 14 ] applied network pharmacology and demonstrated that the active components of Yinqiaosan, that is, luteolin, naringenin, and farnesin, can act on multiple targets, such as tumor necrosis factor (TNF), mitogen-activated protein kinase 1 (MAPK1), and Caspase-3 (CASP3), to regulate signaling pathways, such as Kaposi sarcoma-associated herpesvirus infection, advanced glycation end products (AGE), and their receptors, thereby curing COVID-19.…”
Section: Introductionmentioning
confidence: 99%